(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
This is a short survey in which some questions related to the Zassenhaus Conjecture on finite subgroups in integral group rings are discussed . The bibliography is incomplete but gives a possibility to surch for more references and to find out the details of the subject development.